Endocrine correlates of male polymorphism and alternative reproductive tactics in the Azorean rock-pool blenny, Parablennius sanguinolentus parvicornis - Oliveira, R. F. (2014)
In the Azorean rock-pool blenny male sexual polymorphism occurs. Larger and older males (M1 males) fully express male secondary sex characters (SSC), particularly an anal gland that produces a sex pheromone, whereas smaller and younger sexually active males do not express SSC (M2 males). Two mating tactic types can be identified among M1 males: nest-holders that establish nests and court females and floaters that move around in the breeding area and try to achieve parasitic fertilizations and/or to take over nests. Two behavioral tactic types can also be identified within M2 males: satellites that are associated with particular nests and actively participate in territorial defense (when females go inside the nest to spawn they try to enter to fertilize some of the eggs) and sneakers that do not help nest holders (when spawning occurs they also try to enter the nest to fertilize eggs). It was found that M1 males have significantly higher levels of 11-ketotestosterone (KT), but not testosterone (T), than M2 males [M1 male androgen levels (mean 6 SE): total T 5 11.6 6 3.0 ng ml21, total KT 5 4.5 6 1.1 ng ml21; M2 male androgen levels (mean 6 SE): total T 5 9.6 6 1.0 ng ml21, total KT 5 2.5 6 1.1 ng ml21]. There were no differences in plasma T or KT among individuals using different mating tactics within the same male morph; that is, among M1 males, nest-holders did not differ in androgen levels from floaters [nest-holder androgen levels (mean 6 SE): total T 5 12.3 6 4.4 ng ml21, total KT 5 4.3 6 1.4 ng ml21; floater androgen levels (mean6SE): total T55.960.8 ng ml21, total KT 5 3.4 6 0.3 ng ml21], and among M2 males, satellites did not differ in androgen levels from sneakers [satellite androgen levels (mean 6 SE): total T 5 7.7 6 1.5 ng ml21, total KT51.360.3 ng ml21; sneaker androgen levels (mean6SE): total T58.361.6 ng ml21, total KT 5 1.4 6 0.3 ng ml21]. Thus, the observed differences appear to be correlated with the expression of different male morphotypes and not with the expression of different behavioral tactics within the morphotype. Androgen levels were not correlated with the behavior activity of nest-holders, except for a negative correlation between KT levels and parental behavior. Furthermore, nestholder males that succeeded in having females spawn in their nests during the observation period had significantly lower KT levels than unsuccessful males. Since behavioral observations preceded blood sampling in time, it is suggested that these results indicate a negative relationship between KT and parental care, since successful males were parenting when blood samples were collected. Male SSC were better correlated with KT than with T and the use of total blood levels (i.e., free 1 conjugates) yielded higher correlation coefficients than when only the free fraction of each steroid was considered. Since conjugates are nonactive metabolites of the free androgen they should reflect active free steroids in a previous time. Thus, their incorporation into the hormonal measurements increases the time frame captured, and because steroids are released in a pulsatile way, this time-integrated measure can be more meaningful than the free steroids, which represent a snapshot of the hormone levels at a given point in time.